IT policy and ethics : concepts, methodologies, tools, and applications - IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'IT Policy and Ethics: Concepts, Methodologies, Tools, and Applications is a comprehensive collection of research on the features of modern organizations in order to advance the understanding of IT standards'--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed February 20, 2013).
Keywords: Internet -- Moral and ethical aspects; Information technology -- Moral and ethical aspects; Telecommunication policy -- Moral and ethical aspects; Economics of standardization; ICT's role in development; Information structures; IT policy and ethics; Social issues; Technological innovation and standards